2019
DOI: 10.37190/epe190106
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilisation of tailing ponds with use of water absorbing geocomposites and organic and mineral additives

Abstract: The effectiveness of reclamation activities in a tailing pond has been evaluated by the application of mineral and organic substances and remediation plants with water absorbing geocomposites. The research was conducted on the tailing pond of the former copper mine in Iwiny, Poland, basing on a strict, trifactorial experiment set up with the use of the split-split-plot method with 4 replications. The main experimental factors were the variants of substrate modification, various species (or mixtures) of reclama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The tailings stored in several impoundments, due to their low water capacity, low fertility, high alkalinity and high concentration of residual trace metals, are extremely unfavourable for living organisms (Chodak et al, 2005;Gawron et al, 2007;Krawczyńska et al, 2015;Kasowska et al, 2018). Thus, several attempts were undertaken to improve the tailings physical and chemical properties, aimed to accelerate their biological reclamation, using various kinds of organic substrates, including sewage sludge and geocomposites (Karczewska and Milko, 2010;Karczewska et al, 2011Karczewska et al, , 2013Gersztyn and Karczewska, 2012;Kordas and Tasz, 2012;Spiak et al, 2012;Gersztyn et al, 2013;Marczyk et al, 2013;Kuc et al, 2019).…”
Section: Technogenic Soils In Industrial and Mining Areasmentioning
confidence: 99%
“…The tailings stored in several impoundments, due to their low water capacity, low fertility, high alkalinity and high concentration of residual trace metals, are extremely unfavourable for living organisms (Chodak et al, 2005;Gawron et al, 2007;Krawczyńska et al, 2015;Kasowska et al, 2018). Thus, several attempts were undertaken to improve the tailings physical and chemical properties, aimed to accelerate their biological reclamation, using various kinds of organic substrates, including sewage sludge and geocomposites (Karczewska and Milko, 2010;Karczewska et al, 2011Karczewska et al, , 2013Gersztyn and Karczewska, 2012;Kordas and Tasz, 2012;Spiak et al, 2012;Gersztyn et al, 2013;Marczyk et al, 2013;Kuc et al, 2019).…”
Section: Technogenic Soils In Industrial and Mining Areasmentioning
confidence: 99%
“…The authorities kept secret the results of chemical analyses of the water made immediately after the incident [45,46], and only a few publications have focused on the subject. In the area of the Old Copper Basin, high contents of heavy metals, mainly Cu and Pb, were found in the mining waste, which may have posed a threat to the environment and to the health of the population [47][48][49]. Researchers have shown that although Cu and Pb remain in post-flotation sediments in very poorly soluble forms, there is a risk of increasing their bioavailability, e.g., as a result of some agrotechnical treatments [47].…”
Section: Pollution In Old Copper Basinmentioning
confidence: 99%
“…TSF1 was decommissioned in 1971 and TSF3 was commissioned at the same time and only closed for copper ore mining at the Konrad mine in 1989 [51]. As a result of the postflotation tailings' treatment using technology, the Old Copper Basin areas are very difficult to remediate [43,48,49]. In 1991, TSF1 and 2 were reclaimed by planting poplars, birches, black locust, pines and larches [51].…”
Section: Study Area and Tailings' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Wróblewska et al [94], the application of WAG to soil resulted in an increase of Brunnera macrophylla biomass by up to 360% and the number of leaves by 60%. WAG has also been described as useful in typical engineering applications, in biotechnological structures or in the remediation of degraded areas [5,[95][96][97]. Moreover, a biodegradable version which differs in weaving type and skeleton material is under development [98].…”
Section: Introductionmentioning
confidence: 99%